2020
DOI: 10.3233/prm-200762
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth in pediatric rehabilitation medicine: A survey of clinician reported utilization and experience

Abstract: PURPOSE: Telehealth services have been touted to improve access to specialty pediatric care. COVID-19 accelerated the adoption of telehealth across many medical specialties. The purpose of this study was to examine telehealth utilization and satisfaction among pediatric physiatrists. METHODS: Using Google Forms, a voluntary survey was created and administered to pediatric physiatrists. The survey collected information on practice setting, telehealth utilization, provider satisfaction, perceived satisfaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…TR services have been used to treat conditions such as stroke, traumatic brain injury, multiple sclerosis, chronic pain, hip and knee total arthroplasty, and medical conditions such as congestive heart failure and rheumatologic disease, both by itself and in conjunction with conventional care ( Dietzen et al, 2020 ).…”
mentioning
confidence: 99%
“…TR services have been used to treat conditions such as stroke, traumatic brain injury, multiple sclerosis, chronic pain, hip and knee total arthroplasty, and medical conditions such as congestive heart failure and rheumatologic disease, both by itself and in conjunction with conventional care ( Dietzen et al, 2020 ).…”
mentioning
confidence: 99%
“…A survey study of 78 pediatric PM&R physicians from multiple practice settings (80% academic setting, 13% non‐academic hospital‐based practice, and 7% private practice) reported that 14.5% of respondents used telehealth earlier compared with the use by nearly all (97.4%) since the start of the COVID‐19 pandemic. Most physicians were satisfied (85%) and “strongly agreed” or “agreed” that they would expand their use of telehealth to patients who live in remote geographic areas or have barriers to access clinical care, whereas a majority (57%) planned to expand use for all patients in their practices 145 . A recent cluster‐randomized, crossover study investigating parent and PM&R physician experiences and perceived quality of care between telehealth‐based school health clinic visits and in‐person clinic visits demonstrated that a telehealth model of care for children with special health care needs was equal to an in‐person visit both in experience and perceived quality of care 146 .…”
Section: Cancer Rehabilitation Recommendationsmentioning
confidence: 99%
“…Most physicians were satisfied (85%) and "strongly agreed" or "agreed" that they would expand their use of telehealth to patients who live in remote geographic areas or have barriers to access clinical care, whereas a majority (57%) planned to expand use for all patients in their practices. 145 A recent cluster-randomized, crossover study investigating parent and PM&R physician experiences and perceived quality of care between telehealth-based school health clinic visits and inperson clinic visits demonstrated that a telehealth model of care for children with special health care needs was equal to an in-person visit both in experience and perceived quality of care. 146 Although both studies are descriptive, each suggests high acceptance of telehealth rehabilitation models in pediatric PM&R practice.…”
Section: Pediatric Rehabilitationmentioning
confidence: 99%
“…With the pandemic caused by COVID19, the great need has arisen to maintain remote care for children with disabilities. Evidence suggests many applications in which telehealth can adequately replace traditional in-person visits, and there are many potential applications of telehealth to explore as a means of improving interdisciplinary rehabilitation team connectivity and outreach to pediatric patients (Camden and Silva, 2021; Curfman et al, 2021; Dietzen et al, 2020; Hsu et al, 2021; Maresca et al, 2020; Tenforde et al, 2020).…”
Section: Introductionmentioning
confidence: 99%